Field water balance in beans on a Red-Yellow Latosol - Silveira, Pedro Marques da; Stone, Luiz Fernando (Pesquisa Agropecuaria Brasileira, 2014)
Field water balance in beans (Phaseolus vulgaris L.) was studied on a clay loam Red-Yellow Latosol by the equation: ETa = P - ES ± D ± ∆A. Soil water storage (∆A) calculated down to 0.60 m depth. Internal drainage (D) was estimated based on Darcy's equation which describes water flux in a soil profile. Runoff (ES) was determined using runoff plots. Rainfall (P) was measured with a raingauge. Actual evapotranspiration (Eta) was evaluated by subtraction using the above equation. Evaporation of the Classe A tank (Eo) was also measured. During the 75 day period of this study, the values of P, ES, D, Eta and Eo were 281.80; 19.30; 40.15; 220.47 and 358.07 mm of water, respectively. From the above values Eo was found to be 1.3P, ETa, D and ES were 0.62, 0.11 and 0.05 Eo, respectively. During the periods of germination to flowering, flowering and pod development to maturation, Eta was 3.2; 3.2 and 1.7 mm/day or 0.62; 0.77 and 0.38 Eo, respectively.